Tuneable Thermal Emission Using Chalcogenide Metasurface. Issue 16 (10th June 2018) - Cao, Tun; Zhang, Xinyu; Dong, Weiling; Lu, Li; Zhou, Xilin; Zhuang, Xin; Deng, Junhong; Cheng, Xing; Li, Guixin; Simpson, Robert E.
Abstract: Modulation of thermal radiation is an essential element of infrared sensing and imaging, thermal infrared light sources, camouflage, and thermophotovoltaics. Recently, tuneable thermal emission of nanophotonic structures has been demonstrated. However, most of the current strategies involve controlling single spectral thermal emission in the far‐infrared region, and blue shifting their resonances to the shorter wavelength region is rarely explored. Moreover, fast modulation of multispectral thermal radiation remains challenging. In this work, the dynamic control of multispectral thermal emission from 2 to 4 µm from an ultrathin reconfigurable metasurface is experimentally presented based on Au/SiO2 /Ge2 Sb2 Te5 /Au multilayer. This metadevice contains several integrated thermal emitters of various wavelengths, each of which consists of gold (Au) squares array with different widths. A tuning of multispectral absorptivity (emissivity) can be achieved by transiting the state of Ge2 Sb2 Te5 from amorphous to crystalline. A heat‐transfer model is developed to demonstrate that the reversible switching of multispectral thermal emission can be achieved in just 300 ns. The experimental demonstration along with the theoretical framework lays the foundation for designing high‐speed reconfigurable multispectral thermal emitters, which, as expected, will initiate a new route to thermal engineering. Abstract : Dynamic control of multispectral thermal emission from 2 to 4 µm from an ultrathin reconfigurable chalcogenide metasurface is experimentally presented. This metadevice contains several integrated thermal emitters of various wavelengths each of which consists of an Au squares array with different widths. A tuning of multispectral emissivity is achieved by transiting the state of Ge2 Sb2 Te5 from amorphous to crystalline.